Corporate Leadership, Organizational Factors and Performance of Water Service Companies in Western Region, Kenya - Mangwana, Samson Wando; Odero, Jackline Akoth; Ngoze, Moses (Research Collaboration Community (RCC), 2024)
Corporate leadership is crucial for achieving organizational performance and gaining competitive advantage. It involves operational attributes like structure and culture, and guides individuals and organizations towards achieving their vision. This study sought to examine the influence of corporate leadership on the performance of water service companies in the Western Region, Kenya as moderated by organizational factors. The study was based on transformational leadership theory and institutional theory. The research followed a positivist research philosophy and used a descriptive and correlational research design targeting 245 respondents. For data collection close ended questionnaires were used. Data was analysed using both descriptive and inferential statistics. The study found that corporate leadership had a positive and significant influence on performance of water service companies in Western Region, Kenya whereas organizational factors had a positive though insignificant moderating influence on the relationship between corporate leadership and organizational performance of Water service companies in Western Region, Kenya. The findings extend our knowledge on corporate leadership practices that can enhance performance. The study recommends to government to formulate and execute suitable operational guidelines and policies that would improve in the management of organizations.